2017
DOI: 10.1111/cas.13225
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of nivolumab in Japanese patients with advanced or recurrent squamous non‐small cell lung cancer

Abstract: Limited treatment options are available for stage IIIB/IV non‐small cell lung cancer (NSCLC). Nivolumab, a programmed cell death‐1 immune checkpoint inhibitor antibody, has been shown to be effective for the treatment of NSCLC. The present study investigated the effectiveness and safety of nivolumab in Japanese patients with advanced or recurrent squamous NSCLC that progressed after platinum‐containing chemotherapy. In this multicenter phase II study, patients were treated with nivolumab (3 mg/kg, i.v.) every … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 19 publications
7
52
0
Order By: Relevance
“…Consequently, it was deemed important to assess the effects of nivolumab in the subset of patients expressing PD‐L1. The pooled results of efficacy by PD‐L1 expression in both SQ and non‐SQ NSCLC patients were consistent with those of the individual reports (ONO‐4538‐05, ONO‐4538‐06) . The 3‐year OS and PFS rates showed that, after 3 years of follow‐up, nivolumab continued to demonstrate long‐term efficacy in previously treated patients with SQ or non‐SQ NSCLC.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Consequently, it was deemed important to assess the effects of nivolumab in the subset of patients expressing PD‐L1. The pooled results of efficacy by PD‐L1 expression in both SQ and non‐SQ NSCLC patients were consistent with those of the individual reports (ONO‐4538‐05, ONO‐4538‐06) . The 3‐year OS and PFS rates showed that, after 3 years of follow‐up, nivolumab continued to demonstrate long‐term efficacy in previously treated patients with SQ or non‐SQ NSCLC.…”
Section: Discussionsupporting
confidence: 86%
“…In this analysis of the ONO‐4538‐05 and ONO‐4538‐06 studies, the continued clinical efficacy of nivolumab in Japanese patients with either SQ or non‐SQ NSCLC noted in the primary phase II analysis of this study was reinforced. The safety profile was also found to be acceptable, consistent with that observed in the individual primary analyses …”
Section: Discussionsupporting
confidence: 80%
“…The authors reported a PFS of 126 days (95% CI 42-213), which is higher than that obtained in our study. Even though Hida et al [15] included only squamous NSCLC patients, the confidence interval reported in their study overlapped the PFS value obtained in the present study.…”
Section: Discussionsupporting
confidence: 60%
“…Patients with advanced solid tumors who were treated with nivolumab from March 2009 through to March 2016 at the National Cancer Center Hospital (Tokyo, Japan) were eligible for this study. Subjects included patients who were treated in clinical practice as well as those who participated in sponsor‐initiated investigational trials (ONO‐4538‐01, ONO‐4538‐02, ONO‐4538‐04, ONO‐4538‐05, ONO‐4538‐06, and ONO‐4538‐08) . Patients were excluded from our study for the following reasons: previous treatment with any ICI, pre‐existing hypothyroidism such as thyroid‐stimulating hormone (TSH) >10 μIU/mL or concomitant treatment with levothyroxine replacement therapy before nivolumab, insufficient assessment for thyroid function and thyroid Abs, and a short follow‐up time of less than 90 days from the initial administration of nivolumab to exclude early progression and death.…”
Section: Methodsmentioning
confidence: 99%